Capitalism without Bosses: The Nature of the Firm and Labour-Process under Self-Management - Ferschli, Benjamin (Momentum Quarterly, 2017)
This paper puts forth a theoretical as well as empirical analysis of the firm under “Self-Management” based on elements of the Marxian theory of the firm and related literature. The object of analysis, “Self-Management”, is understood as the suspension of the hierarchical-managerial relationship of command and control, at the point of production, regarding the labour-process of the worker. Institutional Economics, Labour-Process Theory and wider themes from the Sociology of Work are drawn upon to understand data gathered in the course of interviews as well as from a case study. It is argued that self-management, as an apparent fantasy of “capitalism without bosses”, has a distinct presence in the contemporary organisation of labour. The paper further finds that a “control thesis” – derived from the Marxian analysis of the labour contract, which states that capital must control the labour-process – cannot be falsified in the case of the firm under self-management. Further research avenues and consequences for industrial relations are suggested.
Keywords: Labour-Process; self-Management; theory of the Firm